THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND PLACE TOWARDS CUSTOMER SATISFACTION (STUDY IN THE DISTRICT OF SINUIAN VILLAGE SOCIETY REMBOKEN) - Mongkau, Gladis .; Kawet, Lotje .; Sepang, Jantje . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstrack: One of the advantages of traditional markets is the price traders sell bargainable by the buyer, so the price that occurs is the approval of the seller and buyer. Factors that can influence consumer decisions to make purchases can be measured by price variables, service, quality, physical environment, location, and diversity of goods. Consumer satisfaction also means the extent to which the benefits of a product are perceived as expected by the customer. This study aims to find how the influence of product quality, price and place on customer satisfaction in traditional markets Remboken. The population in this study is all consumers who are in the Village District Sinuian Remboken. Sampling technique using Rao Ancient formula, then obtained the total sample of 93 respondents. Data analysis techniques used are the classical assumption test and multiple linear regression analysis with hypothesis testing performed with the F test and t test. The result of analysis shows that product quality, price, and place simultaneously have a significant effect on customer satisfaction in Remboken Traditional Market. Partially, product and price variables have a significant influence on customer satisfaction. Place variable has positive but not significant influence on traditional market of Remboken Sub-district.Keywords: product quality, price, place, consumer satisfaction.